2018
DOI: 10.1080/14737159.2018.1470927
|View full text |Cite
|
Sign up to set email alerts
|

Blood biomarkers and treatment response in major depression

Abstract: Millions of people worldwide suffer from depression, but despite advances in pharmacological therapies, many patients do not experience symptomatic remission or treatment response, even after treatments with several medications. As such, there is an urgent need to identify biomarkers that can not only predict the treatment response but also allow a rational selection of optimal therapy for each patient. Areas covered: This review examines the recent findings, coming from different 'omic sciences,' in human blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 151 publications
0
48
1
3
Order By: Relevance
“…Moreover, our study has the merit to replicate the fine-grained analysis originally presented by Jokela et al (2016) in the largest study reported so far, and to provide support to the link between systemic inflammation and eating behavior in a comparably large population cohort. Finally, our study has also a translational relevance, since inflammatory markers-and especially CRP levels-have often been associated with atypical depression forms, which are more likely to be resistant to treatment with first-line antidepressants, like selective serotonin reuptake inhibitors (SSRI;Chamberlain et al, 2019;Hickman et al, 2014;Köhler-Forsberg et al, 2017;Mora et al, 2018;Strawbridge et al, 2017). Conversely, other classes of antidepressants like monoamine oxidase inhibitors (MAOI) have been reported to be more effective in this sense (Cleare, Fekadu, & Rane, 2012;Łojko & Rybakowski, 2017), and have also been associated with a reduction of oxidative stress and chronic inflammation levels (Sturza et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, our study has the merit to replicate the fine-grained analysis originally presented by Jokela et al (2016) in the largest study reported so far, and to provide support to the link between systemic inflammation and eating behavior in a comparably large population cohort. Finally, our study has also a translational relevance, since inflammatory markers-and especially CRP levels-have often been associated with atypical depression forms, which are more likely to be resistant to treatment with first-line antidepressants, like selective serotonin reuptake inhibitors (SSRI;Chamberlain et al, 2019;Hickman et al, 2014;Köhler-Forsberg et al, 2017;Mora et al, 2018;Strawbridge et al, 2017). Conversely, other classes of antidepressants like monoamine oxidase inhibitors (MAOI) have been reported to be more effective in this sense (Cleare, Fekadu, & Rane, 2012;Łojko & Rybakowski, 2017), and have also been associated with a reduction of oxidative stress and chronic inflammation levels (Sturza et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Overall, previous evidence suggest that somatic depressive symptoms may be more strongly associated with circulating inflammation markers, which are more directly implicated in atypical and treatment-resistant depression forms (Chamberlain et al, 2019;Hickman, Khambaty, & Stewart, 2014;Köhler-Forsberg et al, 2017;Mora, Zonca, Riva, & Cattaneo, 2018;Strawbridge, Young, & Cleare, 2017).…”
Section: Introductionmentioning
confidence: 96%
“…These changes result in a chronic inflammatory response and a disruption of brain integrity and homeostasis as consequence of neuroinflammation [16]. In the brain, glial activation results in the release of cytokines such as tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β), inflammatory mediators that influence the central immune system, modulate neural activity, and regulate the HPA axis [14, 1718]. Chemokines, small chemoattractant proteins, also act as modulators in neuronal transmission and participate in the communication between glia and neurons [8, 19].…”
Section: Introductionmentioning
confidence: 99%
“…3 Several clinical investigations and preclinical studies suggest that inflammatory processes are correlated and could be involved in the onset and/or the progression of MDD, and thus, inflammatory proteins could be used as MDD biomarkers. 4 Indeed, in a large meta-analysis, interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNFalpha), two major pro-inflammatory cytokines, exhibit higher plasma levels in depressed patients compared to controls. 5 Similarly, C-reactive protein (CRP) plasma levels are higher in depressed patients than in healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%